The Influence of Financial Performance on the Stability of Islamic Banks in Indonesia - Agustuty, Lasty; Alam, Andi Rifqah Purnama; Afriyani, Afriyani; Yasin, Nurfatwa Andriani; Hariyanti, Hariyanti (Universitas Muhammadiyah Makassar, 2025)
This study investigates the influence of financial performance on the stability of Islamic banks in Indonesia during the 2018–2023 period. The research uses a quantitative approach with panel data regression analysis conducted through EViews software. The sample consists of five Islamic Commercial Banks (BUS) that regularly publish monthly financial statements. Secondary data were obtained from official bank websites and the Financial Services Authority (OJK). The independent variables in this study include the Capital Adequacy Ratio (CAR), Net Operating Margin (NOM), and Net Performing Financing (NPF), while the dependent variable representing bank stability is proxied by the Z-Score of Return on Assets (ROA). The results reveal that CAR and NOM have a positive and significant impact on the stability of Islamic banks, indicating that strong capital adequacy and profitability enhance resilience and financial soundness. In contrast, NPF shows an insignificant effect on bank stability, suggesting that non-performing financing levels during the observed period were manageable and did not critically threaten financial stability. These findings support both signaling theory and financial intermediation theory, emphasizing that improved capital management and operational efficiency can enhance stakeholder confidence and maintain sustainable stability in Islamic banking. The study contributes to Islamic financial literature by providing empirical evidence on the determinants of financial stability, offering valuable insights for regulators and bank managers in developing strategies to strengthen the resilience of Islamic banking institutions in Indonesia.